The State of Forced Migration and the Main Problems of Internally Displaced Persons in Ukraine - Smyrnova, I.; Chebotarova, V.; Kotelevets, Yu.; Kurbatska, D. (Економічний вісник Донбасу, 2020)
The article considers topical issues of providing social assistance to internally displaced persons. The main problems of internally displaced persons have been identified. It is noted that evaluation, collection of information and its analysis, a comprehensive system of observations identify the state of IDPs, which allows to identify the essence of proper, effective, equitable social development. The state of the normative-legal mechanism of solving the housing problem for IDPs at the national and regional levels is analyzed. Measures to improve the regulatory and legal mechanism for solving the housing problem of internally displaced persons are proposed. У статті розглянуто актуальні питання надання соціальної допомоги внутрішньо переміщеним особам. Визначено основні проблеми внутрішньо переміщених осіб. Відзначено, що оцінювання, збирання інформації та її аналіз, комплексна система спостережень ідентифікують стан вимушеного переселенця, що дає змогу виявити сутність правильного, ефективного, справедливого громадського розвитку. Проаналізовано стан нормативно-правового механізму вирішення житлової проблеми для вимушених переселенців на національному та регіональному рівнях. Запропоновано заходи щодо вдосконалення нормативно-правового механізму вирішення житлової проблеми вимушених переселенців. В статье рассмотрены актуальные вопросы предоставления социальной помощи внутренне перемещенным лицам. Определены основные проблемы внутренне перемещенных лиц. Отмечено, что оценивание, сбор информации и ее анализ, комплексная система наблюдений идентифицируют состояние вынужденного переселенца, который дает возможность проявить сущность правильного, эффективного, справедливого общественного развития. Проанализировано состояние нормативно-правового механизма решения жилищной проблемы для вынужденных переселенцев на национальном и региональном уровнях. Предложены мероприятия по усовершенствованию нормативно-правового механизма решения жилищной проблемы вынужденных переселенцев.